Presence of Bacillus cereus s.l. from ready-to-eat cereals (RTE) products in Sarawak - Lesley Maurice, Bilung; Velnetti, Linang; Kasing, Apun; Yousr, A. N.; Samuel, Lihan (Faculty of Food Science & Technology, UPM., 2013)
Bacillus cereus is a soil inhabitant gram positive bacterium, and is known to cause severe food poisoning. The objective of this study was to isolate and identify the presence of Bacillus cereus s.l. from selected ready to eat cereals purchased randomly from local supermarkets in Kuching and Kota Samarahan, Sarawak. The result showed that four of the 30 food samples were detected to be contaminated by B. cereus s.l. . Our findings suggested that it is important for the public to be aware of the safety of RTE cereals consumption, as it is possible that B. cereus s.l. may be present in high count number and pose hazardous health effects to the consumers.